Engineering of Aerogel-Based Biomaterials for Biomedical Applications - Zheng L; Zhang S; Ying Z; Liu J; Zhou Y; Chen F (International Journal of Nanomedicine, 2020)
Longpo Zheng,1,* Shaodi Zhang,1,* Zhengran Ying,1 Junjian Liu,1 Yinghong Zhou,2– 4 Feng Chen1,4 1Department of Orthopedics, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai 200072, People’s Republic of China; 2The Institute of Health and Biomedical Innovation, Queensland University of Technology, Brisbane, QLD 4059, Australia; 3Key Laboratory of Oral Medicine, Guangzhou Institute of Oral Disease, Stomatology Hospital of Guangzhou Medical University, Guangzhou 510140, People’s Republic of China; 4The Australia-China Centre for Tissue Engineering and Regenerative Medicine (ACCTERM), Queensland University of Technology (QUT), Brisbane, QLD 4000, Australia*These authors contributed equally to this workCorrespondence: Feng Chen Email fchen@tongji.edu.cnAbstract: Biomaterials with porous structure and high surface area attract growing interest in biomedical research and applications. Aerogel-based biomaterials, as highly porous materials that are made from different sources of macromolecules, inorganic materials, and composites, mimic the structures of the biological extracellular matrix (ECM), which is a three-dimensional network of natural macromolecules (e.g., collagen and glycoproteins), and provide structural support and exert biochemical effects to surrounding cells in tissues. In recent years, the higher requirements on biomaterials significantly promote the design and development of aerogel-based biomaterials with high biocompatibility and biological activity. These biomaterials with multilevel hierarchical structures display excellent biological functions by promoting cell adhesion, proliferation, and differentiation, which are critical for biomedical applications. This review highlights and discusses the recent progress in the preparation of aerogel-based biomaterials and their biomedical applications, including wound healing, bone regeneration, and drug delivery. Moreover, the current review provides different strategies for modulating the biological performance of aerogel-based biomaterials and further sheds light on the current status of these materials in biomedical research.Keywords: aerogels, wound healing, bone regeneration, drug delivery, biomedical application